2013
DOI: 10.1590/s0104-42302013000600014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity in asthma and its relations with asthma severity and control

Abstract: This study showed a high prevalence of obesity in asthmatic patients. Obese and non-obese subjects were similar in regard to asthma severity and level of asthma control. Female sex was associated with obesity in this asthma population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…More than half of the patients were females (54%) and this finding is consistent with studies by Agrawal S et al 11 , Forte GC et al 32 and Sposato B et al 28 . And most of these females were housewives which may have been due to greater exposure to fumes and dust at home where chulas are used for cooking.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…More than half of the patients were females (54%) and this finding is consistent with studies by Agrawal S et al 11 , Forte GC et al 32 and Sposato B et al 28 . And most of these females were housewives which may have been due to greater exposure to fumes and dust at home where chulas are used for cooking.…”
Section: Discussionsupporting
confidence: 91%
“…From the above table, it is seen that the studies conducted by Gennuso J et al 21 , Tavasoli S et al 30 and Forte GC et al 32 had similar findings with this study. Other studies had lower prevalence compared to this study.…”
Section: 0%supporting
confidence: 87%
See 1 more Smart Citation
“…Since the prevalence of asthma and obesity have increased over the last decades, a possible association between these two chronic illnesses is suggested [13, 8, 9]. However, literature is inconsistent on the etiology of this association.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the risk on developing asthmatic symptoms rises with increasing Body mass index (BMI) [13]. In addition, some patients demonstrate asthmatic symptoms which are more difficult-to-control with increasing BMI, suggesting a different phenotype [3, 8, 9]. Moreover, the response to asthma medications might be influenced by BMI [3, 9, 10].…”
Section: Introductionmentioning
confidence: 99%